Peran Komunikasi Pelatih PASKIBRA MAN Dairi Dalam Pembentukan Karakter dan Kepemimpinan Anggota - Nur Padillah; Zulfahmi Zulfahmi (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
National education aims not only to foster intellectual development but also to shape the character and civilization of a dignified nation. Within MAN Dairi, this character-building process extends beyond the classroom and also through extracurricular activities. One forum for instilling the values of discipline and responsibility is the Flag Raising Troop (Paskibra). Studies examining the role of Paskibra coaches' communication within the madrasah environment are still relatively limited in developing student character and leadership. The research problem is: What is the role of communication of Paskibra coaches at MAN Dairi in shaping the character and leadership of members? This study uses a qualitative approach with descriptive methods to systematically and factually describe the communication of Paskibra coaches, including instructive, motivational, corrective, and evaluative communication, and their impact on the formation of members' character and leadership. The categorization in this study is as follows: 1). Communication by the Paskibra Trainer, with indicators such as clarity in command delivery, consistency in training rules, and the trainer's assertiveness in giving directions. 2. Character Building, with indicators such as punctuality in training, adherence to rules, and proper task execution. 3. Member Leadership, with indicators such as directing groups/lines, clarity in communication, courage to act in certain situations, and loyalty to the organization. Based on the results of this study, several conclusions were drawn: 1. Communication by the Paskibra Trainer of MAN Dairi in conveying commands to members was clear and focused. 2. Communication by the Paskibra Trainer of MAN Dairi was proven effective in ensuring member compliance with applicable rules. 3. The Paskibra Trainer of MAN Dairi played an effective role in guiding members in carrying out their duties. The direction, guidance, and evaluation provided by the trainer helped members carry out their duties effectively. The trainer's directed communication played a role in shaping members' leadership attitudes relevant to the goal of character building